POLITICAL CAMPAIGN STRATEGY OF TRI RISMAHARINI – ZAHRUL AZHAR IN THE 2024 EAST JAVA GUBERNATORIAL ELECTION - Akbar Faizul Haq; Mohammad Ichlas El Qudsi (Jurnal Komunikasi & Media Digital, 2025)
This research aims to analyze the campaign strategy of Tri Rismaharini and Zahrul Azhar in the 2024 East Java gubernatorial election that targets the teacher community in Surabaya. Using a qualitative case study approach, data were collected through in-depth interviews, document studies, and literature review. The research used cybernetics theory and the campaign model as a research framework. The findings reveal that the Risma–Zahrul campaign strategy combined traditional and digital media, strengthened emotional engagement through social activities, and created two-way communication that enhanced public participation. The study also highlights the active role of teachers as key intermediaries in spreading political messages and building public trust. Based on the findings, it recommends several efforts to strengthen local democracy, including a more intensive dialogue between candidates, the election committee, and educational communities, as well as a school-based political education program and community-driven campaign model.